VILLAGE GOVERNMENT STRATEGY IN MANAGING WATERFALL TOURISM OBJECTS IN PONGKAR VILLAGE, TEBING DISTRICT, KARIMUN REGENCY - Mayang Sary; Rumzy Samin; Edy Akhyary (JPASDEV : Journal of Public Administration and Sociology of Development, 2023)
Tourism in Indonesia according to Tourism Law No. 9 of 1990 article 1 (5) is everything related to tourism and related businesses in their fields. The waterfall located in Pongkar Village, Bing District, Karimun Regency has the potential to be developed into a popular tourist spot for both domestic and foreign tourists. One of the main tourism industries that has the potential to be developed and promoted is waterfalls.  The purpose of this study is  to know the Village Government Strategy in the Management of Waterfall Tourism Objects in Pongkar Village, Tebing District, Karimun Regency with management and development theory according to Karyono. The indicators in this study are: tourism development master plan, as a priority for regional development, development of facilities and infrastructure, procurement of administrative personnel, and tourism promotion. This type of research uses qualitative descriptive analysis techniques with 6 informants. The results of the study (1) The master plan for tourism development has not  been realized due to budget shortfalls, (2) As a priority for regional development, there has been no improvement of damaged infrastructure, (3) The construction of facilities and infrastructure has not been adequate due to budget, (4) Procurement of administrative personnel has not been carried out related to the maintenance of tourist attractions, (5) Tourism Promotion has been carried out related to waterfall attractions.The conclusion of the Village Government Strategy in the management of  waterfall tourism objects in Pongkar Village, Tebing District, Karimun Regency by looking at the Village Government Strategy is still not effective, it can be seen from the lack of management and maintenance of Waterfall attractions. There are problems in the implementation of the management of the Waterfall tourist attraction which is still lacking in budget and neglected facilities and infrastructure in the Waterfall tourist attraction.